Correlation between Invasive and Noninvasive Blood Pressure Measurements in Extremely Low Gestational Age Newborns - Umapathi, Krishna Kishore; Mhanna, Maroun J. (American Journal of Perinatology, 2020)
Objective This work aimed to study the correlation between invasive blood pressure (IBP) and non-IBP (NIBP) in extremely low gestational age newborns (ELGANs) during their first 72 hours of life.Study Design In a retrospective cohort study, IBP and simultaneous NIBP measurements during the first 72 hours of life were recorded in ELGANs. Medical records were reviewed for potential risk factors that affect BP. The % difference in mean arterial BP (% Diff-BP) measurements was calculated as (IBP–NIBP)/IBP. Hypotension was defined as mean arterial Bp < gestational age (GA).Results In total, 236 infants and 1,340 paired IBP–NIBP measurements were studied. Infants had a (mean ± standard deviation) GA of 25.4 ± 21.6 weeks and a birth weight of 810 ± 249 g. Overall, there was a significant correlation between IBP and NIBP of 0.887 (Spearman Rho; p < 0.001). However, the agreement between IBP and NIBP was poor, with a mean difference (95% limits of agreement) of 0.20 (–5.48; 5.89). The mean % Diff-BP (±standard deviation) was 0.39 ± 8.25%. In hypotensive infants, NIBP overestimated IBP measurements, with an agreement of –0.67 (–4.17; 2.83).Conclusion Mean arterial NIBP correlates with IBP in ELGANs. However, there is a poor agreement between methods. In hypotensive infants, NIBP overestimates IBP measurements.
Keywords: invasive; oscillometer; blood pressure; noninvasive; extremely low gestational age newborns